The Image of the Settlers from Kluki in Polish Journalism Presenting the Problem of the Native Population Called Słowińska in the Post-War Period (Until the Mid-1970s) - Malgorzata Mastalerz-Krystjańczuk (Історико-політичні проблеми сучасного світу)
The subject of this research is a journalistic record of settlers arriving after World War II into the village of Kluki, located on Lake Lebsko, which can be found in numerous articles on the fate of the local native population known as Slovinian. Texts on the autochthons began to appear with the end of the war, while the settlers began to be written about in 1947, i.e. after their stay of about a year in Kluki. The newcomers were presented mainly through the prism of conflicts that occurred between some of them and the native population. The numerous crimes committed by several of them at the time affected not only the position of the indigenous people, but also the fact that the settlers from Kluki were associated almost unambiguously with the evil they perpetrated. It was only in the late 1950s that few references began to appear that other newcomers had settled there, who, without breaking the law or entering into conflicts, built their new home under very difficult conditions. In this article, through the compilation of journalistic texts on settlers in Kluki, the basic elements of the image of the immigrant population, which readers received from newspaper reports, were determined. The analysis of the materials provided sufficient data to conclude that this image was definitely one-sided, incomplete, sometimes completely false. With the decline in journalistic interest in the issue of the Slovinians in the 1970s and their eventual departure from Poland, the post-war relations between the autochthons and the settlers ceased to be written about, and the perpetuated image has so far never been analyzed and corrected.